The Influence of Store Layout, Product Display, and Inventory Control on Operational Efficiency at MR.DIY Ngawi and Magetan Branches - Naufal Sandya Sabilillah; Hartirini Warnaningtyas; Muhammad Imron (International Journal of Business and Quality Research, 2026)
Operational efficiency has remained a major concern in the modern retail industry due to intense business competition and the ongoing need to optimize operational costs. While previous studies have separately addressed individual commercial strategies, integrated structural assessments of retail management factors remain sketchy. Therefore, this study examines the predictive role of store layout, product display, and inventory control on operational efficiency at MR.DIY Ngawi and Magetan branches. A quantitative explanatory research design was adopted, while a total saturation census sampling technique was used to select the study population consisting of 30 active employees. Two validated questionnaires were used to collect data from the participants and analyzed using multiple linear regression analysis to test research hypotheses at the level of significance. The result demonstrated that store layout, product display, and inventory control significantly correlated with operational efficiency among study participants, with an Adjusted R Square of 0.881 and an F value of 72.47 at p less than 0.001. Furthermore, store layout (B = 0.493, p = 0.001) and inventory control (B = 0.594, p = 0.001) significantly predicted operational efficiency, whereas product display did not demonstrate a significant partial effect (B = -0.111, p = 0.284). The study concludes that store layout and inventory control significantly contributed to operational efficiency among the study participants. The study recommends that retail stakeholders and store managers should take proactive measures to maintain retail space layouts and execute strict stock control systems to minimize waste and ensure sustained operational efficiency.